The Effectiveness of Teachers’ Use of Lecture Model Combined with Cooperative Learning Method for Enhancing Students’ Problem-Solving Skills in Physics - Rahmi Putri Z; Jumadi Jumadi; Ariswan Ariswan; Ratnasari Ratnasari; Depi Oktasari (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
This study investigates the effect of the use of teachers’ Lecture models combined with cooperative learning methods to improve students’ problem-solving skills in physics compare with the control group who were not exposed to the lecture model combined with cooperative learning methods from effect size value. The research method was a quasi-experimental research. The sample consisted of 33 students of 10th grade in middle schools (senior high school), SMAN 1 Sungai Penuh, Jambi Province where they ware learn at work and energy concept. Students' achievements, as well as their problem-solving skills of work and energy concept were assessed by pretest-posttest with an essay test. The results showed that the experimental group’s learning process has a high effect size value to problem-solving skills more than control group learning process. That shows the lecture model combined with cooperative learning method more effective than lecture model.